CONTRADICTIONS ECONOMIC GROWTH& INVESTOR EXIT IN INDONESIA - Chandra Hendriyani (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2016)
Slowing global economic growth and a decline in the level of trust business institutions in the Euro Area and the United Kingdom to Indonesia contributed to an economic slowdown in Indonesia. Although economic growth in Indonesia alone to increase, but it can not support the climate of the industry that is conducive and increasing purchasing power, as is still needed